Circular RNA Signature in Lung Adenocarcinoma: A MiOncoCirc Database-Based Study and Literature Review - Zhao, Shikang; Li, Shuo; Liu, Wei; Wang, Yanye; Li, Xiongfei; Zhu, Shuai; Lei, Xi; Xu, Song (Frontiers in Oncology, 2020)
Circular RNAs (circRNAs) are a class of endogenous non-coding RNAs (ncRNAs) with a structure of covalently closed continuous loops, which can regulate gene expression by acting as a microRNA sponge or through other mechanisms. Recent studies have identified that the expression of candidate circRNAs are dysregulated in various tumors and hence are considered as promising diagnostic or therapeutic targets across cancer types. However, the expression and function of circRNAs in lung adenocarcinoma (LUAD) remains unclear. In this article, we investigated the expression of circRNAs in LUAD via MiOncoCirc, which is the first and comprehensive database characterizing circRNAs across >2,000 cancer samples using an exome capture RNA sequencing. We identified 7 abnormally expressed circRNAs in LUAD, including circCDR1-AS, circHIPK3, circFNDC3B, circPCMTD1, circRHOBTB3, circFAM13B and circMAN1A2, as well as conducted a literature review about the function and features of these circRNAs. Previous studies have demonstrated that circCDR1-AS, circMAN1A2 and circHIPK3 were upregulated and significantly correlated with a poor survival, or promoted the tumor progression in lung cancer, while other circRNAs have not been fully explored. Besides, we reviewed all the publications regarding circRNAs and LUAD, and noticed that the dysregulation of these circRNAs impacts the development of LUAD through a variety of regulatory mechanisms. In conclusion, the underlying mechanisms of aberrant expression and functions of circRNAs in LUAD are worthy of being further investigated.